PENGENAAN BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN TERHADAP HIBAH WASIAT PASCA PEMBERLAKUAN UNDANG-UNDANG NOMOR 28 TAHUN 2009 TENTANG PAJAK DAERAH DAN RETRIBUSI DAERAH - DWI SARTIKA PARAMYTA (PREMISE LAW JURNAL, 2015)
Under Law No. 28/2009 on PDRD (Regional Retribution and Tax), BPHTB (fees for acquisition of land and building rights) becomes state and local tax. It have the uncertainty of the payable tax is because Article 90, paragraph (1) point d of Law No. 28/2009 does not specify the will certificate, bequest certificate, or the deed of grant made by PPAT; it is the determinant of the payable BPHTB. The uncertainty of the amount of payable tax is related to Article 95, paragraph 4 which does not implicitly specify Perda (Regional Regulation) in regulating the reduction of BPHTB to bequest. It is recommended that article 90, paragraph (1), point d of Law No. 28/2009 on PDRD which regulates the payable BPHTB, states that the bequest should be revised to be the date it is made and signed of  the deed of acquisition of land and building rights. Meanwhile, Article 95, paragraph 4 on reducing tax in certain area (including BPHTB), which can be regulated by Perda on state and local tax, should comply with legal provisions by eliminating Article 95, paragraph (4) and amended it to Article 95, paragraph (3). Keywords: Tax, Right Acquisition, Land and Building, Bequest